Autosomal dominant ApoA4 mutations present as tubulointerstitial kidney disease with medullary amyloidosis - Kmochová, Tereza; Kidd, Kendrah O; Orr, Andrew; Hnízda, Aleš; Hartmannová, Hana; Hodaňová, Kateřina; Vyleťal, Petr; Naušová, Karolína; Brinsa, Vítězslav; Trešlová, Helena; Sovová, Jana; Barešová, Veronika; et al. (Kidney international, 2024)
Sporadic cases of apolipoprotein A-IV medullary amyloidosis have been reported. Here we describe five families found to have autosomal dominant medullary amyloidosis due to two different pathogenic APOA4 variants. A large family with autosomal dominant chronic kidney disease (CKD) and bland urinary sediment underwent whole genome sequencing with identification of a chr11:116692578 G>C (hg19) variant encoding the missense mutation p.L66V of the ApoA4 protein. We identified two other distantly related families from our registry with the same variant and two other distantly related families with a chr11:116693454 C>T (hg19) variant encoding the missense mutation p.D33N. Both mutations are unique to affected families, evolutionarily conserved and predicted to expand the amyloidogenic hotspot in the ApoA4 structure. Clinically affected individuals suffered from CKD with a bland urinary sediment and a mean age for kidney failure of 64.5 years. Genotyping identified 48 genetically affected individuals; 44 individuals had an estimated glomerular filtration rate (eGFR) under 60 ml/min/1.73 m2, including all 25 individuals with kidney failure. Significantly, 11 of 14 genetically unaffected individuals had an eGFR over 60 ml/min/1.73 m2. Fifteen genetically affected individuals presented with higher plasma ApoA4 concentrations. Kidney pathologic specimens from four individuals revealed amyloid deposits limited to the medulla, with the mutated ApoA4 identified by mass-spectrometry as the predominant amyloid constituent in all three available biopsies. Thus, ApoA4 mutations can cause autosomal dominant medullary amyloidosis, with marked amyloid deposition limited to the kidney medulla and presenting with autosomal dominant CKD with a bland urinary sediment. Diagnosis relies on a careful family history, APOA4 sequencing and pathologic studies.
Keywords: Nephritis, Interstitial; medullary amyloidosis; Renal Insufficiency, Chronic; autosomal dominant tubulointerstitial kidney disease; Humans; Amyloidosis; AApoA-IV; ApoA4; amyloidóza; lidé středního věku; apolipoproteiny A; Middle Aged; mutace; chronická renální insuficience; lidé; Mutation; intersticiální nefritida; Apolipoproteins A